2006
DOI: 10.1128/jvi.00673-06
|View full text |Cite
|
Sign up to set email alerts
|

Latent Kaposi's Sarcoma-Associated Herpesvirus Infection of Endothelial Cells Activates Hypoxia-Induced Factors

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV or HHV-8) is the etiological agent of Kaposi's sarcoma, a highly vascularized, endothelial-derived tumor. A direct role for KSHV-mediated induction of angiogenesis has been proposed based upon the nature of the neoplasia and various KSHV gene overexpression and infection model systems. We have found that KSHV infection of endothelial cells induces mRNA of hypoxia-induced factor 1␣ (HIF1␣) and HIF2␣, two homologous alpha subunits of the heterodimeric transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
113
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 59 publications
5
113
0
Order By: Relevance
“…This increase is in line with many cancer cells in culture (13). We previously showed that HIF transcriptional activity is increased by KSHV infection of endothelial cells (6). Hypoxia increases the stability of HIFs and HIF protein levels and activity are synergistically increased by KSHV infection combined with the hypoxia mimic, desferoxamine (Dfo) (6).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…This increase is in line with many cancer cells in culture (13). We previously showed that HIF transcriptional activity is increased by KSHV infection of endothelial cells (6). Hypoxia increases the stability of HIFs and HIF protein levels and activity are synergistically increased by KSHV infection combined with the hypoxia mimic, desferoxamine (Dfo) (6).…”
Section: Resultsmentioning
confidence: 56%
“…We previously showed that HIF transcriptional activity is increased by KSHV infection of endothelial cells (6). Hypoxia increases the stability of HIFs and HIF protein levels and activity are synergistically increased by KSHV infection combined with the hypoxia mimic, desferoxamine (Dfo) (6). When KSHV-infected cells were treated with Dfo, there was also a large synergistic increase in glucose uptake (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The expression and transcriptional activity of HIF-1a are up-regulated in KSHV-infected endothelial cells (33). To identify KSHV proteins that affect HIF1a activity, we surveyed several KSHV proteins for their potential effects on HIF-1a activity using the luciferase construct containing six repeats of HRE.…”
Section: Resultsmentioning
confidence: 99%
“…Latent infection with HHV-8 is associated with the endothelial tumor Kaposi's sarcoma (KS) in AIDS patients and others with lowered immunity, and KS lesions in vivo are associated with high levels of both the HIF-1α and HIF-2α protein [45]. HHV-8 infection of endothelial cells in vitro leads to increased stabilization of the two HIF α subunits and increased HIF-responsive gene expression [45].…”
Section: Hif-1α Dynamics In Viral Infectionmentioning
confidence: 99%
“…Latent infection with HHV-8 is associated with the endothelial tumor Kaposi's sarcoma (KS) in AIDS patients and others with lowered immunity, and KS lesions in vivo are associated with high levels of both the HIF-1α and HIF-2α protein [45]. HHV-8 infection of endothelial cells in vitro leads to increased stabilization of the two HIF α subunits and increased HIF-responsive gene expression [45]. The HHV-8 latency-associated nuclear antigen (LANA), which plays a critical role in modulating viral and target cell gene expression, increases HIF-1α mRNA levels, and also physically interacts with the transcription factor to enhance its promoter activities [46].…”
Section: Hif-1α Dynamics In Viral Infectionmentioning
confidence: 99%